Tuberculosis Masquerading Foreign Body in Children - Hosseinali Ghaffaripour; Maedeh Asi; Ali Valinejadi; Maryam Hassanzad; Tayyebeh Khakkard; Arda Kiani; Leila Mohammadpour (International Journal of Mycobacteriology)
Foreign body aspiration (FBA) is a common issue in children, particularly boys, and can be life-threatening. Early removal of the foreign body (FB) leads to recovery, but delayed diagnosis may cause complications such as granuloma, recurrent pneumonia, and atelectasis. This condition often results from a child’s curiosity, with factors such as inadequate swallowing reflex and activity during eating contributing to the risk. The right bronchus is the most common site for FB impaction. In this case, a child presented with persistent productive cough and shortness of breath. Initial computed tomography scans suggested pneumonia and mucoid impaction in the right lung, raising concern for tuberculosis due to a family history. However, further ultrasound and clinical findings confirmed FBA. The FB, a pen cap, was removed via bronchoscopy, and the patient’s symptoms resolved. Follow-up care was provided to ensure continued recovery.